Harmonizing FORIN for climate change adaptation & disaster risk management to develop multi-sectoral narratives for Metro Manila - Gotangco, Charlotte Kendra Z (Archīum Ateneo, 2013)
Policy and development planning initiatives in the Philippines currently recognize the need for the mainstreaming of climate change adaptation (CCA) and disaster risk management (DRM). Given the connections between climate and extreme weather events, a holistic framework that integrates CCA and DRM would allow for the analysis of common variables that affect risk and resilience to both climate change and disaster impacts. This project therefore aimed (1) to adapt the in-depth “Forensic Investigation” (FORIN) framework for disaster analyses into a comprehensive CCA-DRM framework, (2) to operationalize the framework by developing FORIN narratives focused on Metro Manila, and (3) to attempt to connect key variables, processes and trends into a systems model structure. The narratives encompassed the physical, social, economic and health sectors. Project output included (1) the CCA-DRM Addendum to the FORIN Report, (2) the multi-sectoral narratives for Metro Manila, and (3) sectoral causal loop diagrams and preliminary systems model structures. Project implementation highlighted the need for leveling-off and deeper communication among sectors to evolve a truly interdisciplinary approach to the characterization of risk and a consistent paradigm for a systems model. This project was intended as a preliminary scoping activity in preparation for deeper FORIN analyses and is in conjunction with a larger project, the International Research Initiative on Adaptation to Climate Change (IRIACC) Coastal Cities at Risk (CCaR) project.